Design And Construction Of An Arduino Based Farming Group Watering System - Lily Gabriella (International Journal of Industrial Innovation and Mechanical Engineering, 2024)
Muncan Village has various farmer groups , one of which is the "Sertile Mentandur Farmers Group," which adopts an organic approach to crop cultivation, especially rice. The irrigation system used in Muncan Village, especially for rice fields, is the pekasih system. This system works by opening irrigation channels from rice fields to rice fields that will receive distribution water when it is their turn, while irrigation channels to rice fields that are not currently receiving distribution will be closed. In the research conducted, researchers used research methodology to examine the problems encountered. In designing the Watering Technology Prototype for the Subur Mentandur Farmer Group in Muncan Village based on Arduino, researchers collected data through observation, interviews and literature studies using the Research and Development (R&D) research method. The aim of this research is to assist the Subur Mentandur Farmers Group in managing the delivery of irrigation water remotely via smartphone using short messages.